2019
DOI: 10.21608/aeji.2019.33973
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Radiofrequency Ablation Combined with either Percutaneous Ethanol Injection or Percutaneous Acetic Acid Injection in the Management of Hepatocellular Carcinoma.

Abstract: Results: Evaluation of the response one month later using triphasic CT showed significant better responses in GII compared to GI (83.3% vs 60%) with P value <0.05. The response 3 months later was not changed significantly compared to the response after one month of the procedure (56.7% in GI and 80% in GII) Conclusion: Ablation of inoperable large HCC 5.1-7cm can be done with combined techniques. RFA plus acetic acid was compared to RFA plus ethyl alcohol. Complete ablation was superior when acetic acid was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Another study done at Menoufia university, Egypt, compared single local ablative and combined techniques in HCC. The combined locoregional method provided better results[ 143 ]. However, Kamal et al [ 144 ] found no difference between MWA ablation and RFA ablation in treating HCC.…”
Section: Treatment Of Hcc In Egyptmentioning
confidence: 99%
“…Another study done at Menoufia university, Egypt, compared single local ablative and combined techniques in HCC. The combined locoregional method provided better results[ 143 ]. However, Kamal et al [ 144 ] found no difference between MWA ablation and RFA ablation in treating HCC.…”
Section: Treatment Of Hcc In Egyptmentioning
confidence: 99%